Outdoor super-durability stone carving product protection processing method
Patent Information
- Application Number
- CN202610545073.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-04-23
AI Technical Summary
[0002]目前,室外石雕产品长期暴露于自然环境中,容易导致冻融循环导致的微裂纹扩展、酸雨带来的化学腐蚀、以及霉菌或青苔造成的生物污染与外观劣化,目前行业内现有的加工防护技术主要是在石雕表面涂上防护涂料,干燥后形成涂层,存在以下缺陷:
现有技术中石雕加工防护采用常温涂刷物理涂层法,物理涂层渗透深度仅1mm~2mm。本发明将石雕预热温度控制在50℃~65℃,纳米无机强化液温度控制在25℃~35℃,形成温和的梯度温差,该温差既能产生微观负压辅助渗透,又避免了热应力对石雕结构的损伤,渗透石雕内部的毛细孔隙的深度可达3mm~6mm,相比传统工艺渗透深度更深,且大幅降低了加工废品率。
Smart Images

Figure CN122187517B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of stone processing technology, and in particular to a protective processing method for outdoor ultra-durable stone carving products. Background Technology
[0002] Currently, outdoor stone carvings are exposed to the natural environment for extended periods, making them susceptible to micro-crack propagation due to freeze-thaw cycles, chemical corrosion from acid rain, and biological contamination and deterioration caused by mold or moss. Existing processing and protection technologies in the industry primarily involve applying a protective coating to the stone carving surface, which, after drying, forms a coating layer. However, this approach has the following drawbacks: When applied by brushing or spraying at room temperature, the protective coating penetrates only shallowly, typically only 1 to 2 millimeters. As the surface of the stone carving weathers naturally, the protective coating quickly becomes ineffective. Furthermore, this type of protective coating only provides waterproofing and cannot improve the original structural strength of the stone, offering limited help in resisting freeze-thaw cracking.
[0003] Moreover, the coating is not breathable, so the moisture or humidity that originally formed inside the stone carving cannot evaporate. Once it gets cold and freezes, the coating will peel, crack, and fall off, seriously damaging the artistic beauty of the stone carving. Summary of the Invention
[0004] Therefore, in view of the above problems, the present invention proposes a protective processing method for outdoor ultra-durable stone carving products, which solves the above problems.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A protective processing method for outdoor ultra-durable stone carving products includes the following steps: Step S1: Carve the stone sculpture and collect the scraps and debris generated during the carving process; After the carving is completed, the dust on the surface of the stone carving is cleaned using ultrasonic equipment. Then the stone carving is placed in a heating device and heated to 50℃~65℃ in stages, and then kept warm to ensure that the capillary pores on the surface and inside of the stone carving are heated evenly and that the free water located in the capillary pores evaporates. Furthermore, the scraps and debris are crushed to form homogeneous stone powder with a particle size distribution between 500nm and 2μm; Step S2: Prepare the nano-inorganic strengthening liquid and preheat it to 25℃~35℃. Add the homogeneous stone powder obtained in step S1 to the nano-inorganic strengthening liquid at a mass ratio of 5%. While the stone carving is kept at the temperature of the heat preservation treatment in step S1, the nano-inorganic strengthening liquid containing homogeneous stone powder is evenly applied to the surface of the stone carving by atomization. Utilizing the temperature difference between the internal temperature of the stone carving and the temperature of the nano-inorganic strengthening liquid, combined with capillary action, the nano-inorganic strengthening liquid containing homogeneous stone powder is drawn into the capillary pores 3mm~6mm away from the surface of the stone carving, and then the drying process is carried out. The nano-inorganic strengthening liquid comprises, by mass percentage: 8%~15% nano-silica sol, 5%~10% lithium silicate, 0.3%~0.8% penetrating nonionic surfactant, and the balance being deionized water; Step S3: After the stone carving treated in step S2 is completely dry, clean the surface of the stone carving with a neutral cleaning agent and dry the stone carving until the moisture content is below 5%. Step S4: Apply an inorganic-organic hybrid protective agent containing perhydropolysilazane and perfluoroalkylsilane to the surface of the stone carving at room temperature. Step S5: Move the stone carving into the environmental control room for static curing, inducing the inorganic-organic hybrid protective agent to hydrolyze and crosslink on the surface of the stone carving and in the capillary pores 3mm to 6mm away from the surface of the stone carving, transforming it into a silica network skeleton.
[0006] Furthermore, in step S1, the frequency of the ultrasonic device is 20KHz~30KHz, the heating rate of each stage of the stepped heating is controlled between 1℃ / min and 2℃ / min, and the holding time is 2 hours to 3 hours.
[0007] Furthermore, in step S2, the pH value of the nano-inorganic strengthening liquid is controlled between 10 and 11.
[0008] Furthermore, in step S3, the neutral cleaning agent is a 3%~5% (v / v) aqueous solution of citric acid or an aqueous solution of ammonium bicarbonate; Clean the surface of the stone carving with a neutral cleaning agent, then rinse it thoroughly with deionized water, and dry it at 40℃~50℃ until the moisture content of the stone carving is less than 5%.
[0009] Furthermore, in step S4, the inorganic-organic hybrid protective agent comprises, by mass percentage: 8%~12% of room temperature curing perhydropolysilazane, 5%~8% of perfluorodecyltrimethoxysilane, 0.3%~1.0% of crosslinking accelerator, and the balance being an environmentally friendly dearomatic hydrocarbon solvent or isoparaffin solvent.
[0010] Furthermore, in step S5, the temperature of the environmental control room is set to 20℃~30℃, the relative humidity is precisely controlled between 50%~65%, and the static curing time is 48 hours~72 hours.
[0011] By adopting the aforementioned technical solution, the beneficial effects of the present invention are: Existing technologies for stone carving processing and protection employ a room-temperature physical coating method, with a penetration depth of only 1mm to 2mm. This invention controls the preheating temperature of the stone carving at 50℃ to 65℃ and the temperature of the nano-inorganic strengthening liquid at 25℃ to 35℃, creating a gentle temperature gradient. This temperature difference generates microscopic negative pressure to aid penetration while avoiding thermal stress damage to the stone carving structure. The penetration depth into the capillary pores inside the stone carving can reach 3mm to 6mm, which is deeper than traditional processes and significantly reduces the scrap rate.
[0012] The nano-inorganic strengthening liquid, which combines nano-silica sol and lithium silicate, retains the strengthening function of lithium silicate reacting with calcium ions inside the stone carving to form calcium silicate crystals and seal microcracks, thereby improving compressive strength. At the same time, the filling effect of nano-silica reduces the presence of free alkali. Combined with the subsequent cleaning steps with neutral cleaning agents, it solves the problem of traditional inorganic hardeners being prone to alkali return.
[0013] The induced inorganic-organic hybrid protective agent undergoes hydrolysis and cross-linking on the surface of the stone carving and within capillary pores 3mm to 6mm thick, transforming into a Si–O–Si network framework. Specifically, the cured perhydropolysilazane undergoes a deamination hydrolysis reaction under moisture-induced conditions to form a Si–O–Si network framework; the hydrophobic groups of the perfluoroalkylsilane are firmly anchored, forming a micro-nano-scale hydrophobic surface, which can effectively prevent UV aging and provide long-lasting protection. Attached Figure Description
[0014] Figure 1 This is a front view schematic diagram of the pulverizer structure of the present invention.
[0015] Figure 2 This is a front view schematic diagram of the outer shell structure of the present invention.
[0016] Figure 3 This is a top view schematic diagram of the crusher structure of the present invention.
[0017] Figure 4 This is a partial structural plan view of the crushing mechanism of the present invention.
[0018] Figure 5 This is a schematic plan view of the first, second, and third crushing rollers of the present invention in use.
[0019] Numbering on the map: 1. Outer shell; 101. Guide groove; 2. Feed inlet; 3. Crushing mechanism; 4. Spiral blades; 5. Discharge outlet; 6. First motor; 7. Receiving tank; 8. Powder outlet; 9. Screen; 101. Guide groove; 301, First crushing roller; 302, Second crushing roller; 303, Driven gear; 304, Meshing gear; 305, Second motor; 306, Drive gear; 307, Third crushing roller; 308, Extrusion roller; 309, Trapezoidal ridge; 310, Trapezoidal depression; 311, Groove. Detailed Implementation
[0020] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments.
[0021] A protective processing method for outdoor ultra-durable stone carving products includes the following steps: Step S1: Carve the stone sculpture and collect the scraps and debris generated during the carving process; The stone carving is made of granite.
[0022] After the carving is completed, the dust on the surface of the stone carving is cleaned using ultrasonic equipment. Then the stone carving is placed in a heating device and heated to 50℃~65℃ in stages, and then kept warm to ensure that the capillary pores on the surface and inside of the stone carving are heated evenly and to evaporate the free water located in the capillary pores inside the stone carving. Furthermore, the scraps and debris are crushed to form homogeneous stone powder with a particle size distribution between 500nm and 2μm.
[0023] In this step, the heating equipment is existing equipment. The heating rate of the heating equipment for the stone carving is controlled between 1℃ / min and 2℃ / min, and the holding time is 2 hours to 3 hours.
[0024] The frequency of the ultrasonic device is 20KHz~30KHz.
[0025] Step S2: Prepare the nano-inorganic strengthening liquid and preheat it to 25℃~35℃. Add the homogeneous stone powder obtained in step S1 to the nano-inorganic strengthening liquid at a mass ratio of 5%. While the stone carving is kept at the temperature of the heat preservation treatment in step S1, the nano-inorganic strengthening liquid containing homogeneous stone powder is evenly applied to the surface of the stone carving by atomization. Utilizing the temperature difference between the internal temperature of the stone carving and the temperature of the nano-inorganic strengthening liquid, combined with capillary action, the nano-inorganic strengthening liquid containing homogeneous stone powder is drawn into the capillary pores 3mm~6mm away from the surface of the stone carving, and then the drying process is carried out. The nano-inorganic strengthening liquid comprises, by mass percentage: 8%~15% nano-silica sol, 5%~10% lithium silicate, 0.3%~0.8% penetrating nonionic surfactant, and the balance being deionized water.
[0026] Preferably, the pH value of the nano-inorganic strengthening liquid is controlled between 10 and 11.
[0027] Step S3: After the stone carving treated in step S2 is completely dry, clean the surface of the stone carving with a neutral cleaning agent and dry it until the moisture content of the stone carving is less than 5%.
[0028] The neutral cleaning agent is a citric acid aqueous solution or an ammonium bicarbonate aqueous solution with a volume concentration of 3% to 5%.
[0029] Furthermore, after cleaning the stone carving surface with a neutral cleaning agent, it can be thoroughly rinsed with deionized water and dried at 40℃~50℃ until the moisture content of the stone carving is less than 5%.
[0030] Step S4: Apply an inorganic-organic hybrid protective agent containing perhydropolysilazane and perfluoroalkylsilane to the surface of the stone carving at room temperature.
[0031] Specifically, the inorganic-organic hybrid protective agent comprises, by mass percentage: 8%~12% of room temperature curing perhydropolysilazane, 5%~8% of perfluorodecyltrimethoxysilane, 0.3%~1.0% of crosslinking accelerator, and the balance being an environmentally friendly dearomatic hydrocarbon solvent or isomeric alkane solvent.
[0032] Step S5: Move the stone carving into the environmental control room for static curing, inducing the inorganic-organic hybrid protective agent to hydrolyze and crosslink on the surface of the stone carving and in the capillary pores 3mm to 6mm away from the surface of the stone carving, transforming it into a silica network skeleton.
[0033] Specifically, the temperature in the environmental control room is set at 20℃~30℃, the relative humidity is precisely controlled between 50%~65%, and the static curing time is 48 hours~72 hours.
[0034] In this embodiment, the above-mentioned protective processing method for outdoor ultra-durable stone carving products is used for the protective processing of outdoor granite stone carvings, wherein: In step S1, a 25kHz ultrasonic cleaning device is used in conjunction with deionized water to perform atomized cleaning on the surface of the granite sculpture to remove dust contaminants. The cleaned sculpture is then pushed into a heating device and heated from room temperature to 60℃ at a rate of 1.5℃ / min. The temperature is maintained for 2.5 hours to fully evaporate the deep free water located in the capillary pores of the sculpture.
[0035] Step S2: Prepare the nano-inorganic strengthening solution by mass percentage: 12% nano-silica sol, 8% lithium silicate, 0.5% penetrating nonionic surfactant, and the remainder is deionized water. Adjust the pH value to 10.5.
[0036] Homogeneous stone powder is added to the nano-inorganic strengthening liquid at a mass ratio of 5% and mixed evenly. The nano-inorganic strengthening liquid containing homogeneous stone powder is preheated to 30°C. While maintaining the surface temperature of the stone carving at 60°C, the nano-inorganic strengthening liquid is applied evenly using a low-pressure atomization spraying device. The mixture is left to stand for 30 minutes to allow the nano-inorganic strengthening liquid to fully penetrate, and then allowed to dry naturally for 12 hours. The penetrating nonionic surfactant is alkylphenol polyoxyethylene ether.
[0037] Step S3: Prepare a 4% citric acid aqueous solution as a neutral cleaning agent. Apply the solution evenly to the surface of the stone carving with a soft brush. After 5 minutes, rinse with deionized water using high-pressure atomization until the surface pH value is neutral. Place the stone carving in a 45℃ drying room to dry until the moisture content is below 5%.
[0038] Step S4: Prepare the inorganic-organic hybrid protective agent by mass percentage: 10% room-temperature curing perhydropolysilazane, 6% perfluorodecyltrimethoxysilane, 0.5% crosslinking accelerator, and the remainder is an isoparaffin solvent. Apply the agent evenly to the stone carving surface using an air-assisted spraying device at room temperature, controlling the spraying amount to 80 g / m². 2 ²~100g / m 2 .
[0039] Step S5: Move the sprayed stone sculpture into the environmental control room, set the temperature to 25℃ and the relative humidity to 60%, and let it stand for 72 hours for curing. During the curing process, the cured perhydropolysilazane undergoes a hydrolysis and condensation reaction under the action of moisture, transforming into a dense silica network skeleton. At the same time, the hydrophobic segments of perfluoroalkylsilane are arranged in an orderly manner on the surface to form a superhydrophobic protective layer.
[0040] Testing showed that the granite carving surface treated in this embodiment is effectively waterproof, with an effective penetration depth of 5.2mm. The compressive strength is increased by 28.6% compared to the untreated carving. After 50 freeze-thaw cycles, specifically from -20℃ to 20℃, and 12 hours per cycle, the surface showed no cracks or peeling.
[0041] In a comparative test, four granite samples of the same material were selected and carved into stone sculptures of the same shape. Different coatings were applied to the sculptures for blood-protection treatment. The effective penetration depth, compressive strength of the sculptures after 2000 hours of QUV accelerated aging, and surface cracking and efflorescence were tested using 50 freeze-thaw cycles. Sample A: The stone carving is left untreated; Sample B uses existing technology to coat the surface of the stone carving with a polyurethane film. Sample C uses existing technology to coat the surface of the stone carving with a sodium silicate film; Sample D was processed using the aforementioned outdoor ultra-durable stone carving product protective processing method on the stone carving surface.
[0042] The results of the comparative tests are shown in the table below: Effective penetration depth none 1.3 mm 7.2 mm 5.2 mm Improved compressive strength 0% 7% 31% 28.6% 50 freeze-thaw cycles test Surface microcracks Surface microcracks The stone carving has micro-cracks on its surface, and the coating is yellowing and peeling. intact Alkali return phenomenon No obvious alkali return Slight efflorescence Obvious white discharge No obvious alkali return Test results show that, while ensuring penetration depth and protective performance, the present invention effectively solves the risk of stone carving cracking and efflorescence caused by the high-temperature rapid cooling method, and its overall performance is significantly better than that of the existing technology.
[0043] While performing step S1, collect the scraps and debris of the same material generated during the stone carving process, and crush them using a crusher for 1 to 2 hours until homogeneous stone powder with a particle size distribution between 500 nm and 2 μm is obtained.
[0044] The homogeneous stone powder obtained is added to the nano-inorganic strengthening liquid in step S2 at a mass ratio of 5%. During construction in step S2, the nano-inorganic strengthening liquid containing homogeneous powder is injected into the heated and expanded capillary pores through low-pressure atomization. Since the pulverized powder is consistent with the material of the stone carving, the filling structure formed in the pores has the same coefficient of thermal expansion as the stone carving, which greatly enhances the structural strength of the subsurface layer and further improves the adhesion of the subsequent hybrid protective agent.
[0045] refer to Figures 1-5 The pulverizer includes a housing 1, a feed inlet 2 located at the top of the housing 1, a pulverizing mechanism 3 located at the feed inlet 2, a spiral blade 4 located below the feed inlet 2 and rotatably located at the bottom of the housing 1, a discharge port 5 located on the right side of the housing 1 and at the right end of the spiral blade 4, a first motor 6 for driving the spiral blade 4 to rotate, a receiving tank 7 for connecting to the discharge port 5, and a powder outlet 8 located on the outside of the housing 1 and spaced apart from the receiving tank 7. The housing 1 is provided with a screen 9 at the powder outlet 8.
[0046] The crushing mechanism 3 includes a first crushing roller 301 rotatably mounted on the outer casing 1, a second crushing roller 302 parallel to the first crushing roller 301, a driven gear 303 located on one transverse side of the first crushing roller 301, a meshing gear 304 located on one transverse side of the second crushing roller 302, a second motor 305 located above the meshing gear 304, and a driving gear 306 located at the output shaft of the second motor 305 and meshing with the driven gear 303. The outer casing 1 contains a rotatably mounted first crushing roller 301 and second crushing roller 302. A third crushing roller 307 is located below the center of the crushing roller 302. One side of the third crushing roller 307 is connected to the first crushing roller 301 via a synchronous belt (not marked in the figure). The gaps between the third crushing roller 307 and the first crushing roller 301, and between the third crushing roller 307 and the second crushing roller 302, are smaller than the gap between the first crushing roller 301 and the second crushing roller 302. A squeeze roller 308 is located at the midpoint of the perpendicular line where the first crushing roller 301, the second crushing roller 302, and the third crushing roller 307 intersect. The perpendicular line can be referenced. Figure 5The dotted lines in the diagram indicate that the first crushing roller 301 has a raised trapezoidal ridge 309 on its outer side, the second crushing roller 302 has a trapezoidal recess 310 on its outer side for cooperating with the trapezoidal ridge 309, the third crushing roller 307 has a plurality of grooves 311 on its outer side, the width and depth of the grooves 311 being smaller than the width and depth of the trapezoidal recesses 310, and the outer side of the outer shell 1 has a guide groove 101 for the transverse movement of the extrusion roller 308.
[0047] In operation, the first motor 6 drives the spiral blades 4 at the bottom of the outer casing 1, and the second motor 305 drives the drive gear 306 to rotate. The drive gear 306 drives the meshing gear 304 to rotate through the driven gear 303, thereby causing the first crushing roller 301 and the second crushing roller 302 to rotate simultaneously. The first crushing roller 301 drives the third crushing roller 307 to rotate through the synchronous belt. After the scrap and debris are poured in from the feed port 2, they will reach between the first crushing roller 301 and the second crushing roller 302. The trapezoidal protrusions 309 on the outer side of the first crushing roller 301 and the trapezoidal recesses 310 on the outer side of the second crushing roller 302 will crush the scrap and then drop it above the extrusion roller 308. When the trapezoidal protrusion 309 engages with and then rotates away from the trapezoidal recess 310, the trapezoidal protrusion 309 on the first crushing roller 301 will be tangent to the outer surface of the extrusion roller 308, causing the extrusion roller 308 to move to the left. At this time, the trapezoidal recess 310 on the outer side of the second crushing roller 302 will rotate and approach the position of the extrusion roller 308. The extrusion roller 308 partially presses into the trapezoidal recess 310 of the second crushing roller 302, further extruding the crushed scrap into a finer state. Then, after the trapezoidal recess 310 on the outer side of the second crushing roller 302 leaves the extrusion roller 308, the extrusion roller 308 will be pushed to the right end, extruding between the trapezoidal protrusions 309 of the first crushing roller 301. After the scrap material is processed, it reaches above the third crushing roller 307. Because the gap between the third crushing roller 307 and the first crushing roller 301 and the second crushing roller 302 is smaller, the crushed scrap material is squeezed by the trapezoidal protrusions 309 on the outer sides of the first and second crushing rollers 301 and the groove 311 of the third crushing roller 307. The crushed scrap material is then ground into fine powder. This primary compression by the first and second crushing rollers 301 and the secondary grinding by the third crushing roller 307 below creates a stepped processing path of coarse and fine crushing. Due to the smaller gap between the third crushing roller 307 and the first crushing roller 301, and the smaller gap between the third crushing roller 307 and the second crushing roller 302... The gaps between rollers 302 and 302 are all smaller than the gap between the first crushing roller 301 and the second crushing roller 302. The compressive strength of the material gradually increases during the falling process, ensuring that the scraps can be fully crushed into fine powder, which significantly improves the fineness of the finished product. By utilizing the phase change of the trapezoidal convex rib 309 and trapezoidal concave 310 during the rotation process, the middle extrusion roller 308 is driven to reciprocate. Utilizing the power margin, the extrusion roller 308 forms a dynamic alternating extrusion between the first crushing roller 301 and the second crushing roller 302, which performs secondary high-frequency kneading and compaction on the initially crushed material, effectively avoiding the problem of uneven crushing caused by the material directly passing through the gap in traditional crushers.
[0048] The trapezoidal protrusions 309 of the first crushing roller 301 and the trapezoidal recesses 310 of the second crushing roller 302 form a contour-following fit, which can generate a strong shearing force to process large pieces of scrap. The fine grooves 311 of the third crushing roller 307 provide more grinding contact points for fine particles. This design combining coarse and fine textures enhances the equipment's adaptability to different sizes of debris, enabling some scrap to be ground into powder. The bottom of the equipment is equipped with spiral blades 4, which can force the crushed powder and scrap fragments to the right-side discharge port 5. This not only solves the problem of fine powder easily accumulating and clumping at the bottom of the outer shell 1, but also ensures the continuity of discharge. With the external receiving tank 7, a closed and dust-free collection process is achieved. The screen 9 located at the bottom of the outer shell 1 near the receiving tank 7 allows fine powdery scrap to pass through the screen 9 and be discharged from the powder outlet 8, thus performing initial screening of powdery scrap and large pieces of scrap. The entire process of feeding, crushing, extrusion, grinding and discharging can be completed by only two sets of motors. In particular, inside the crushing mechanism 3, the transmission between the driving gear 306 and the driven gear 303, combined with the linkage design of the extrusion roller 308, makes great use of the internal space of the equipment, reducing energy consumption and equipment size.
[0049] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0050] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0051] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0052] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0053] Although the invention has been specifically shown and described in conjunction with preferred embodiments, those skilled in the art should understand that various changes in form and detail may be made to the invention without departing from the spirit and scope of the invention as defined in the appended claims, all of which shall be within the scope of protection of the invention.
Claims
1. A protective processing method for outdoor ultra-durable stone carving products, characterized in that, Includes the following steps: Step S1: Carve the stone sculpture and collect the scraps and debris generated during the carving process; after carving, use ultrasonic equipment to clean the dust on the surface of the stone sculpture, then place the stone sculpture in a heating device, use a stepped heating method to raise the temperature to 50℃~65℃, and keep it warm to ensure that the capillary pores on the surface and inside of the stone sculpture are heated evenly and evaporate the free water located in the capillary pores; and then crush the scraps and debris to form homogeneous stone powder with a particle size distribution between 500nm and 2μm. Step S2: Control the pH value of the nano-inorganic strengthening liquid between 10 and 11, and preheat it to 25°C to 35°C. Add the homogeneous stone powder obtained in step S1 to the nano-inorganic strengthening liquid at a mass ratio of 5%. While the stone carving is kept at the temperature of the heat preservation treatment in step S1, apply the nano-inorganic strengthening liquid containing homogeneous stone powder evenly to the surface of the stone carving by atomization. Utilize the temperature difference between the internal temperature of the stone carving and the temperature of the nano-inorganic strengthening liquid, combined with capillary action, to draw the nano-inorganic strengthening liquid containing homogeneous stone powder into capillary pores 3mm to 6mm thick from the surface of the stone carving. Then, perform drying treatment. The nano-inorganic strengthening liquid comprises, by mass percentage: 8%~15% nano-silica sol, 5%~10% lithium silicate, 0.3%~0.8% penetrating nonionic surfactant, and the balance being deionized water; Step S3: After the stone carving treated in step S2 is completely dry, clean the surface of the stone carving with a neutral cleaning agent and dry the stone carving until the moisture content is below 5%. Step S4: Apply an inorganic-organic hybrid protective agent containing perhydropolysilazane and perfluoroalkylsilane to the surface of the stone carving at room temperature; Step S5: Move the stone carving into an environmental control room for static curing, inducing the inorganic-organic hybrid protective agent to hydrolyze and crosslink on the surface of the stone carving and in the capillary pores 3mm to 6mm away from the surface of the stone carving, transforming it into a silica network skeleton.
2. The method for protective processing of outdoor ultra-durable stone carving products according to claim 1, characterized in that: In step S1, the frequency of the ultrasonic device is 20KHz~30KHz, the heating rate of each stage of the stepped heating is controlled between 1℃ / min and 2℃ / min, and the holding time is 2 hours to 3 hours.
3. The method for protective processing of outdoor ultra-durable stone carving products according to claim 1, characterized in that: In step S3, the neutral cleaning agent is a citric acid aqueous solution or an ammonium bicarbonate aqueous solution with a volume concentration of 3% to 5%. After cleaning the stone carving surface with the neutral cleaning agent, it is thoroughly rinsed with deionized water and dried at 40℃ to 50℃ until the moisture content of the stone carving is less than 5%.
4. The protective processing method for outdoor ultra-durable stone carving products according to claim 1, characterized in that: In step S4, the inorganic-organic hybrid protective agent comprises, by mass percentage: 8%~12% of room temperature curing perhydropolysilazane, 5%~8% of perfluorodecyltrimethoxysilane, 0.3%~1.0% of crosslinking accelerator, and the balance being an environmentally friendly dearomatic solvent or isoparaffin solvent.
5. The protective processing method for outdoor ultra-durable stone carving products according to claim 1, characterized in that: In step S5, the temperature of the environmental control room is set to 20℃~30℃, the relative humidity is precisely controlled between 50%~65%, and the static curing time is 48 hours~72 hours.
Citation Information
Patent Citations
Method for making novel material capable of overcoming defects of sculpture component material
CN107759183A
Preparation process of waterproof retro carved gypsum decorative plate
CN112143324A